Islamic Business Ethics in Student Start-Up Development - Muhammad Umar Maya Putra; Muhammad Habibi Siregar; Nurhayati Nurhayati (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: The Student Creativity Program in Entrepreneurship (SCP) initiated by the Indonesian Ministry of Education, Culture, Research, and Technology aims to strengthen student entrepreneurship through innovation, market analysis, and ethical business practices. This study examines how Islamic business ethics contribute to strengthening marketing, operational, financial, and business planning aspects within the SCP framework. Method: This research employs a qualitative descriptive approach using a literature review method. Data were collected from books, scientific articles, national journals, and official SCP program documents, and analyzed through descriptive qualitative techniques with triangulation to ensure validity. Results: The findings indicate that SCP encourages evidence-based entrepreneurial decision-making through systematic market research, product innovation, and digital-based business development. From the perspective of Islamic business ethics, entrepreneurial practices must align with the principles of fiqh al-mu'amalah, emphasizing honesty, fairness, transparency, and accountability. Marketing activities should reflect ethical conduct consistent with Islamic legal and moral principles. Operational decisions integrate rational analysis with maqasid al-shariah through tahqiq al-manath. Financial practices prohibit gharar (uncertainty), unjust enrichment, and deceptive transactions, while business planning emphasizes accountability and transparency as reflected in the Qur'anic concept of al-tijarah. Conclusion: The integration of Islamic business ethics within the SCP framework demonstrates that student entrepreneurship can simultaneously pursue economic viability, ethical responsibility, and social benefit. By aligning entrepreneurial activities with Sharia-based ethical values, the program contributes to developing innovative start-ups and morally grounded, socially responsible entrepreneurs in Indonesia.